Effects of employee social capital on wage satisfaction, job satisfaction and organizational commitment - Christoph Hauser (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
The article proposes that basic social attitudes and associational networks of employees influence their interaction with coworkers and managers at the workplace and thereby also shape work attitudes and behavior. Two terms are introduced to analyze this hypothesis: Civic Social Capital (denoting personal trust and associational activity) and Workplace Social Capital (social interaction with colleagues and trust towards management). Based on a survey of 1007 employees I demonstrate the impact of social trust and two forms of institutional trust (confidence towards national and regional institutions) on a composite index of workplace social capital. In addition, social and institutional trust also influence work related attitudes such as perception of a fair wage, job satisfaction and organizational commitment. Once workplace social capital is controlled for in regressions on work related attitudes, social trust becomes insignificant. Thus, workplace social capital serves as a transmission mechanism converting social trust in enhanced rates of both wage/job satisfaction and in particular organizational commitment. In contrast, confidence towards regional institutions exerts a sustained impact on work related attitudes that persists alongside the impact of social interaction with colleagues and management.
Keywords: Z1; Z13; J24; J28; 330; Civic Social Capital; Social Trust; Institutional Trust; Workplace Social Capital; Job Satisfaction; Organizational Commitment